Synchronous Translation – a Complex Set of Cognitive Processes - Z.Z., Gafarova; M.A. , Bozorova; Sh.Sh., Jumayeva; L.I. , Idiyeva; L.U. , Radjabova (International Journal of Psychosocial Rehabilitation, 2020)
Synchronous translation is one of the most advanced types of translation in terms of complexity. In addition to translating what you hear and translate it at the same time, listening to the speaker’s next speech requires a translator to be proficient and strong minded. This requires considering the cognitive abilities of the interpreter and studying the mental processes that occur in his or her thinking